A revision of Prescottia (Orchidaceae: Orchidoideae, Cranichideae) - Azevedo, Cecilia O. De; Berg, Cássio Van Den; Barros, Fábio De (Phytotaxa, 2014)
This study of Prescottia is based on fieldwork, in situ observations and study of herbarium material. Fifteen species are recognised for Prescottia: P. carnosa, P. densiflora, P. ecuadorensis, P. glazioviana, P. lancifolia, P. leptostachya, P. lojana, P. montana, P. mucugensis, P. oligantha, P. ostenii, P. phleoides, P. plantaginifolia, P. spiranthophylla, and P. stachyodes. Seven lectotypifications, one neotypification, and six new synonymies are proposed. Prescottia spiranthophylla is re-established, and three nomina nuda are listed. Descriptions, a key to the species, illustrations, and distribution maps are provided.